2023
DOI: 10.1038/s41420-023-01340-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital color-coded molecular barcoding reveals dysregulation of common FUS and FMRP targets in soma and neurites of ALS mutant motoneurons

Abstract: Mutations in RNA binding proteins (RBPs) have been linked to the motor neuron disease amyotrophic lateral sclerosis (ALS). Extensive auto-regulation, cross-regulation, cooperation and competition mechanisms among RBPs are in place to ensure proper expression levels of common targets, often including other RBPs and their own transcripts. Moreover, several RBPs play a crucial role in the nervous system by localizing target RNAs in specific neuronal compartments. These include the RBPs FUS, FMRP, and HuD. ALS mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Moreover, knockdown of HuD decreased mutant FUS-induced apoptosis in vitro and, strikingly, knockdown of the related elav Drosophila gene completely rescued motor phenotypes induced by FUS in vivo. We have recently shown that in MNs FUS mutation or HuD overexpression exert similar effects in the expression of disease-linked genes (Garone et al, 2023). Altogether, these findings point to a crucial role for HuD in the cell autonomous mechanisms that underlie the death of MNs via a "dying back" pattern in FUS and, possibly, a subset of sporadic ALS cases with hallmarks of oxidative and proteotoxic stress.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, knockdown of HuD decreased mutant FUS-induced apoptosis in vitro and, strikingly, knockdown of the related elav Drosophila gene completely rescued motor phenotypes induced by FUS in vivo. We have recently shown that in MNs FUS mutation or HuD overexpression exert similar effects in the expression of disease-linked genes (Garone et al, 2023). Altogether, these findings point to a crucial role for HuD in the cell autonomous mechanisms that underlie the death of MNs via a "dying back" pattern in FUS and, possibly, a subset of sporadic ALS cases with hallmarks of oxidative and proteotoxic stress.…”
Section: Discussionmentioning
confidence: 82%
“…This could be due to the combined effects of downregulation of miR-375, a HuD targeting miRNA (De Santis et al, 2017), and direct binding of mutant FUS to HuD 3'UTR, resulting in competition between mutant FUS and FMRP for HuD 3'UTR binding (De Santis et al, 2019;Garone et al, 2021). Increased HuD levels in FUS WT MNs produce changes in the transcriptome that are substantially similar to those exerted by the severe FUS P525L variant (Garone et al, 2023). A direct consequence of HuD upregulation in FUS mutant iPSCderived MNs and mouse spinal cord is an increase of the levels of two previously known HuD targets, Neuritin1 (NRN1; also known as cpg15) and GAP43 (Garone et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, knockdown of HuD decreased mutant FUS-induced apoptosis in vitro and, strikingly, knockdown of the related elav Drosophila gene completely rescued motor phenotypes induced by FUS in vivo . We have recently shown that in MNs FUS mutation or HuD overexpression exert similar effects on the expression of disease-linked genes (Garone et al, 2023). Altogether, these findings point to a crucial role for HuD in the cell-autonomous mechanisms that underlie the death of MNs via a “dying back” pattern in FUS and, possibly, a subset of sporadic ALS cases with hallmarks of oxidative and proteotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we have previously shown that mRNA and protein levels of HuD, encoded by the ELAVL4 gene, are upregulated in MNs derived from FUS mutant human induced pluripotent stem cells (iPSCs) and in a mouse model (Fus-Δ14 knock-in) (Garone et al, 2021). Increased HuD levels in FUS WT MNs produce changes in the transcriptome that are substantially similar to those exerted by the severe FUS P525L variant (Garone et al, 2023). A direct consequence of HuD upregulation in FUS mutant iPSC-derived MNs and mouse spinal cord is an increase in the levels of its targets, including Neuritin1 (NRN1; also known as cpg15) and GAP43 (Garone et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation